Penyuluhan Budidaya Burung Puyuh sebagai Usaha untuk Memajukan Dunia Wirausaha Bagi Generasi Petani Millenial di Dusun Krebet Kecamatan Srengat Kabupaten Blitar - Rachmawati, Danar Nanda; Susilo, Eko Adi; Herdina Nafiana (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service (PkM) activity focuses on the implementation of Quail Cultivation Counseling as a strategic effort to advance entrepreneurship among the Millennial Farmer Generation in Krebet Hamlet, Srengat, Blitar. This activity was motivated by the high economic potential of Quail and the need to improve the entrepreneurial competence of the younger generation in the livestock sector. The main goal of the program is to transform traditional cultivation into a structured, efficient, and sustainable modern business unit. The implementation method combines theoretical knowledge transfer with practical assistance in the field. The counseling material includes three pillars: 1) Business Scale Management, including capital management and strategies for increasing livestock population; 2) Quality Management and Livestock Health, emphasizing cage sanitation, feed, and quality vitamins; and 3) Marketing strategies to expand the distribution network. The results of the activities showed high effectiveness. Quantitatively, 80% of Millennial Farmer participants succeeded in implementing post-extension livestock population increases. Qualitatively, this activity fosters awareness, motivation, and a strategic entrepreneurial mindset so that participants are able to face production and market challenges. With this strategic practice, quail businesses are expected to increase profitability and competitiveness. This PKM serves as a catalyst in supporting economic independence and entrepreneurial development of the younger generation in the agribusiness sector.